MODEL KOMUNIKASI CAMPUR KODE PARA PEDAGANG ARAB TERHADAP JEMAAH UMRAH INDONESIA DI KOTA MADINAH - Khairawati Khairawati; Nursukma Suri; Suwarto Suwarto (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
The friendship and brotherhood of Arabs and Indonesians in terms of politics, social, religion, art, economy and culture is part of the undoubted cooperation both in bilateral agreements and in political recognition of these Arab countries. Arabic to Indonesian people through language communication, causing code mixing in the language. So, the influence of Arabic is very strong in Indonesian. Code mixing is a form of Social Exchange, which is a communication model that has an attitude of interconnectedness between individuals. In communication there is an element of reward in the form of profit (profit) and sacrifice (cost). From this model what traders do in offering or promoting goods sold by traders in the city of Medina to Umrah pilgrims. Mixed communication codes that are used to give meaning and can be understood in the process of buying and selling. Mix the codes used in the form of inserting words, phrases, repetition of words, idioms and clauses such as assalamualaikum, look around, look for clothes, which one, ana loss, anta turid, marhaba-marhaba, la yumkin, and how much is the equivalent. This qualitative research uses the method of proficient free-talk, note-taking and recording techniques, namely recording on data cards using writing instruments, then recording techniques.